Solubility of baclofen in 1-hexyl-4-methylpyridinium bromide + water binary mixtures - Abbas Mehrdad; Sahar Ehsani-Tabar; Sara Taeb (شیمی کاربردی روز, 2017)
In this paper, solubility of baclofen was studied by gravimetric method. The solubility of baclofen was measured in (water + 1-hexyl-4-methylpyridinium bromide) binary mixtures from 293.1 K to 313.1 K under atmosphere pressure. In binary mixtures, the solubility increases with increasing ionic liquid concentration. This behavior probably is due to hydrophobic interaction between ACP and ionic liquid and formation of micelle. Indeed ionic liquid similar to the conventional cationic surfactants have tendency to associate as micelle structures. The main responsible to enhancement the solubility of baclofen in lower mass fraction is hydrophobic interaction between baclofen and ionic liquid. Whereas, in upper mass fractions of ionic liquid, beyond hydrophobic interactions, the formed micelles are another possible reason behind enhanced solubility of baclofen in aqueous solution of ionic liquid. The solubility data were fitted using modified Apelblat equation, and the semi-empirical λh equation. Both equations were shown a good applicability to prediction on solubility of baclofen in aqueous solutions of ionic liquid.